Revitalizing Local Wisdom: The Pataru Indahan Tradition in Mandailing Society - Harahap, Mawaddatun Nikmah; Asari, Hasan (Journal of Social Work and Science Education, 2025)
This study aims to examine the revitalization efforts of local wisdom values embedded in the Pataru Indahan tradition, a traditional seven-month pregnancy ceremony practiced by the community of Hajoran Village, Sungai Kanan Subdistrict, South Labuhanbatu Regency. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, participatory observation, and documentation to obtain a comprehensive and contextual understanding of the tradition's implementation and transformation. The findings indicate that revitalizing the Pataru Indahan tradition requires synergy among traditional leaders, village authorities, educational institutions, and active community involvement, particularly from younger generations. Identified revitalization strategies include integrating the tradition into non-formal education, strengthening the local cultural narrative, and embedding traditional values into social and communal activities. This study offers a contextual and participatory approach to revitalization, emphasizing the importance of youth engagement and the reinforcement of cultural values within the framework of modern social life. The findings provide a strategic foundation for local stakeholders to design culturally adaptive preservation programs that respond to social change while remaining relevant to contemporary community life. This study contributes to the literature on cultural anthropology and local tradition preservation by presenting a participatory-based revitalization model that can be applied to other cultural traditions facing existential decline due to modernization.